Application of the Kaiser score to increase diagnostic accuracy in equivocal lesions on diagnostic mammograms referred for MR mammography. Issue 134 (January 2021) - Jajodia, Ankush; Sindhwani, Geetika; Pasricha, Sunil; Prosch, Helmut; Puri, Sunil; Dewan, Ajay; Batra, Ullas; Doval, Dinesh Chandra; Mehta, Anurag; Chaturvedi, Arvind K
Highlights: Kaiser score overcomes potential shortcomings of moderate inter-reader agreement of BIRADS lexicon and provides higher diagnostic accuracy. Score <4 was helpful in subcategorizing previously assigned ACR-BIRADS 4 lesions into probably benign category in 85.7 %. Score >=8 was highly suggestive of malignancy in 100 % of previously assigned ACR-BIRADS 4 lesions, thus significantly improving certainty. Unnecessary biopsies could have been avoided using the Kaiser score clinical decision tool in 60.8 % cases. Abstract: Introduction: We aimed to interpret MR mammography (MRM) using the Kaiser scores for equivocal or inconclusive lesions on mammography (MG). Methods: Retrospective IRB-approved evaluation of 3623 MG for which MRM was deployed as a problem-solving tool, after inclusion-exclusion criteria were met. Three readers with different levels of experience assigned a final score from 1 to 11 based on the previously established tree classification system. Area under the curve (AUC) derived from receiver operating characteristic (ROC) analysis was used to determine the overall diagnostic performance for all lesions and separately for mass and non-mass enhancement. Sensitivity, specificity, and likelihood ratio values were obtained at different cut-off values of >4, > 5, and > 8 to rule in and rule out malignancy. Result: Histopathology of 183 mass and 133 non-mass enhancement (NME) lesions show benign etiology in 95 and malignant in 221. The AUC was 0.796 [0.851 for mass and 0.715 for NME]. Applying the Kaiser score upgraded 202 lesions with correct prediction in 77 %, and downgraded 28 lesions with correct prediction in 60.8 %. Using a score <5 instead of <4 to rule out malignancy improved our diagnostic ability to correctly identify 100 % benign lesions. Applying Kaiser score correctly downgraded 60.8 % (17/28) lesions; thus avoiding biopsies in these. Using a high cut-off value>8 to rule-in malignancy, we correctly identified 59.7 % of lesions with 80 % specificity and positive likelihood ratio of 3. Conclusion: The Kaiser score has clinical translation benefits when used as a problem-solving tool for inconclusive MG findings.